Who eats whom in the Barents Sea? - Bjarte Bogstad (NAMMCO Scientific Publications, 2000)
An overview of the estimates of consumption by predators on the main fish stocks in the Barents Sea is given. The main predators are cod (Gadus morhua), harp seal (Phoca groenlandica) and minke whale (Balaenoptera acutorostrata). The results indicate that cod is the most important predator, consuming about as much food annually as harp seals and minke whales combined. The consumption estimates, together with data on the amount of fish removed by commercial fisheries, are compared to estimates of the abundance and removal through natural mortality of the various species of fish prey. The consistency between these estimates is discussed. The natural mortality values for cod and haddock used in assessments are found to be reasonably consistent with the consumption estimates. The consumption of capelin is found to be higher than what is available for predation in years of low capelin abundance, while in years of high herring abundance the consumption of herring does not explain all the mortality. The way in which the consumption estimates are and can be utilised in the assessment and management of fish stocks in the Barents Sea using multispecies models and approaches is described.